HISTORICAL BACKGROUND AND PROSPECTS FOR DEVELOPMENT OF NAVAL STATE UNIVERSITY, BILIRAN, PHILIPPINES - Francisco M. Ebio, Jr (Researchers World - International Refereed Social Sciences Journal, 2021)
The study generally aimed to trace the historical background of Naval State University (NSU) in Naval, Biliran, Philippines and relate the findings thereof to the prospects for development of the school. It used the historical and descriptive methods of research involving 256 respondents. NSU humbly started as Naval High School in 1946 then Naval Institute of Technology in 1974. There were rising and falling trends in the enrolment and graduation in the different curricular offerings of NSU except in the Colleges of Engineering and Arts and Sciences which enjoyed a constant increase in enrolment. The school plant and instructional facilities of NSU were perceived “adequate” by the respondents. For the next ten years, NSU’s degree profile program for faculty and employees, school plant, instructional facilities and linkage with various agencies for absorption of graduates may have been improved. In addition, education, engineering, AB, BS and other related courses may have been offered in NSU. A study may be conducted on the causes and effects of the various trends in the enrolment and graduation in the different curricular offerings of NSU and that, the prospective courses considered “high priority” especially those rated “highest priority” be offered in NSU ten years to come.